Energy management using battery intervention power supply integrated with single phase solar roof top installations. (15th November 2018) - Kamala Devi, V.; Premkumar, K.; Bisharathu Beevi, A.
Abstract: In India, battery storage and time based tariff are yet to be introduced in solar micro grid tied inverters. Here, the authors propose an improved multi-stage converter topology intended for single phase solar roof top applications with battery storage. It works in six modes depending on solar-load-battery-grid profiles. The whole strategy is implemented in a battery intervention power supply that uses energy storage integrated with the solar generator that helps in smoothing of power, load shifting, load dispatch and load angle control. Notably, load dispatch decision is arrived based on several independent parameters that take different values at a time. A Boolean equation is derived relating the different parameters so as to arrive at a single decision. This is achieved by a variable entity k-map. A voltage control is also implemented that is done by load angle control of the inverter current. A novel MPPT scheme is also detailed that reduces oscillations in PV voltage during steady state and dynamic behavior of environmental conditions. Simulation studies are conducted to analyse the performance of the system using improved power management using k-map, modified MPPT algorithm and steady state and dynamic conditions of atmosphere under varying load-solar-grid profiles. The performance is validated by testing a prototype laboratory model that shows that the system works with acceptable limits of reactive compensation in the range of 95–99% with good grid stability through battery support. Highlights: Power quality improvement using filters. Battery storage. Different inverter topologies. Optimization strategies. Voltage regulation.